The concept of coıınselor of tenth grade (Lycee 2) girls in a Turkish school compared with their concepts of teacher, mother and confidante - Manyasiğ, Yeşim. (Thesis (M.A.)- Bogazici University. Institute of Social Sciences, 1979., 2021)
The role and the function of the counselor is difficult to define, because counseling is a new profession. Studies in the American literatüre show that only some of the children in schools with established guidance programs have developed an idea of what the counselor should be doing. In Turkey the guidance counseling movement is cotnparatively new, therefore it is quite probable that the ideas of counseling and the role of the counselor in the school are quite vague in the minds of many people. The present descriptive study tried to investigate the meaning of the concept of counselor of a small select group of Turkish female students who had been exposed to counseling, in compa rison to the meaning of the concepts of mother, teacher and confidante of the same students, It was felt that the individuals represented by the concepts of mother, teach er and c onfi dante were ali people whose func tions and roles might conveivably overlap at times with the concept of the counselor, making it difficult for students to distinguish them and causing students to assign certain cha racteristics in common to several or ali of them. Further it was felt that since some of the concepts were perhaps more familiar to the majority of the students than others, (e.g. concept of mother versus concept of counselor) that, sensing a relationship between concepts, they would perhaps assign some of the attributes of the more well-known concepts to the coposelor. Subjects for the study were selected frora among students of Üsküdar American College for Girls, Lycee 2 class (lûth grade) who had been exposed to some counseling and who were at an age to be able to distinguish between counselor, mother, teacher and confidante. The students rated each of the above concepts, counselor, mother, teacher and confidante on a semantic differential scale of nine bipolar adjectives and the Wilcoxon test was applied to the data received. The results showed that the students did not statistically differentiate among the four concepts in terms of the bipolar adjective check list. This was interpreted to mean that there was no significant difference in the rating intensities of adjectives for the four concepts. However, there was a ten dency in student's responses to rate the mother and the con» f_i_dajvte more favorably than either the counselor or the teacher, who was given the least favorable ratings among ali four.
Keywords: Educational counseling -- Turkey.